Expression of Bottom Component RNA of Cowpea Mosaic Virus in Cowpea Protoplasts - Rezelman, Geertje (1980)
Upon inoculation of cowpea protoplasts with the bottom component of cowpea mosaic virus, at least six virus-induced proteins (with sizes of 170, 110, 87, 84, 60, and 32 kilodaltons) are synthesized, but not the capsid proteins (37 and 23 kilodaltons). These bottom-component-induced proteins were studied with respect to their genetic origin and mode of synthesis. The analyses were based on their electrophoretic peptide patterns resulting from partial digestion with Staphylococcus aureus protease V8. Comparison of the peptide patterns of the virus-induced proteins with those of the cowpea mosaic virus RNA-coded polypeptides produced in rabbit reticulocyte lysate showed that the 170- and 32-kilodalton polypeptides, which are the first viral products in cowpea mosaic virus-infected cells, were actually coded by the bottom component RNA of the virus. The 110-, 87-, and 84-kilodalton polypeptides, and possibly the 60-kilodalton polypeptide, appeared to have amino acid sequences in common with the 170-kilodalton polypeptide, demonstrating that they were virus coded as well. The results indicated that cowpea mosaic virus bottom component RNA was translated in vivo into a single 200-kilodalton polyprotein from which probably all bottom-component-specific proteins arose by three successive cleavages.